Microencapsulation of Rambutan Peel Extract by Spray Drying - Luis Boyano-Orozco; Tzayhrí Gallardo-Velázquez; Ofelia Gabriela Meza-Márquez; Guillermo Osorio-Revilla (Foods, 2020)
Microencapsulation of bioactive compounds (BC) from rambutan peel by spray drying using DE10 maltodextrin as encapsulating agent was performed. The optimal conditions for the ethanolic extraction of BC were 60 °C, with a time of 1 h, 55% aqueous ethanol and three extraction cycles. The best spray drying encapsulating conditions for BC and antioxidant capacity (AC) were: inlet temperature 160 °C, outlet temperature 80 °C, and 10% encapsulating agent concentration in the feeding solution (core:encapsulating agent ratio of 1:4). With these conditions, retention and encapsulation efficiencies obtained were higher than 85%, the water activity value, moisture content and Hausner Index were of 0.25 ± 0.01, 3.95 ± 0.10%, and 1.42 ± 0.00, respectively. The optimized powder presented good solubility and morphological properties, showing microcapsules without ruptures. Based on these results, microencapsulation by spray drying is a viable technique which protects BC of rambutan peel, facilitating its application in the food, pharmaceutical, and cosmetic industries.